The Influence of Ancient Greece: A Historical and Cultural Analysis - Dane Carter (GoAcademica Research & Publishing, 2023)
This scholarly article delves into the profound impact of Ancient Greece on the development of Western civilization. The article explores various aspects of Ancient Greek society, including philosophy, politics, arts, and architecture, and highlights their lasting contributions that continue to shape modern thought and culture. By analyzing key historical events, prominent figures, and significant cultural achievements, this paper seeks to provide a comprehensive understanding of the enduring legacy of Ancient Greece.